A Nonovershooting Controller with Integral Action for Multi-input Multi-output Drug Dosing Control⁎. Issue 4 (2018) - Padmanabhan, Regina; Meskin, Nader; Ionescu, Clara M.; Haddad, Wassim M.
Abstract: In this paper, a nonovershooting tracking controller is proposed for the continuous infusion of multiple drugs that have interactive effects. The proposed controller design method exploits the freedom of eigenstructure assignment pertinent to the design of feedback controllers for multi-input, multi-output (MIMO) systems. For drug dosing, a nonovershooting tracking controller restricts the undesirable side effects of drug overdosing. The proposed tracking controller is based on an estimate of the full state using a hybrid extended Kalman filter (EKF) that is used to reconstruct the system states from the measurable system outputs. An integral control action is included in the controller design to achieve robust tracking in the presence of patient parameter uncertainty. Simulation results and performance analysis of the proposed control strategy are also presented using 20 simulated patients.